Risks and Benefits of Early Rhythm Control in Patients With Acute Strokes and Atrial Fibrillation: A Multicenter, Prospective, Randomized Study (the RAFAS Trial) - Junbeom Park; Jaemin Shim; Jung Myung Lee; Jin‐Kyu Park; JoonNyung Heo; Yoonkyung Chang; Tae‐Jin Song; Dong‐Hyeok Kim; Hye Ah Lee; Hee Tae Yu; Tae‐Hoon Kim; Jae‐Sun Uhm; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background The purpose of the RAFAS (Risk and Benefits of Urgent Rhythm Control of Atrial Fibrillation in Patients With Acute Stroke) trial was to explore the risks and benefits of early rhythm control in patients with newly documented atrial fibrillation (AF) during an acute ischemic stroke (IS). Method and Results An open‐label, randomized, multicenter trial design was used. If AF was diagnosed, the patients in the early rhythm control group started rhythm control within 2 months after the occurrence of an IS, unlikely the usual care. The primary end points were recurrent IS within 3 and 12 months. The secondary end points were a composite of all deaths, unplanned hospitalizations from any cause, and adverse arrhythmia events. Patients (n=300) with AF and an acute IS (63.0% men, aged 69.6±8.5 years; 51.2% with paroxysmal AF) were randomized 2:1 to early rhythm control (n=194) or usual care (n=106). A total of 273 patients excluding those lost to follow‐up (n=27) were analyzed. The IS recurrences did not differ between the groups within 3 months of the index stroke (2 [1.1%] versus 4 [4.2%]; hazard ratio [HR], 0.257 [log‐rank P=0.091]) but were significantly lower in the early rhythm control group at 12 months (3 [1.7%] versus 6 [6.3%]; HR, 0.251 [log‐rank P=0.034]). Although the rates of overall mortality, any cause of hospitalizations (25 [14.0%] versus 16 [16.8%]; HR, 0.808 [log‐rank P=0.504]), and arrhythmia‐related adverse events (5 [2.8%] versus 1 [1.1%]; HR, 2.565 [log‐rank P=0.372]) did not differ, the proportion of sustained AF was lower in the early rhythm control group than the usual care group (60 [34.1%] versus 59 [62.8%], P<0.001) in 12 months. Conclusions The early rhythm control strategy of an acute IS decreased the sustained AF and recurrent IS within 12 months without an increase in the composite adverse outcomes. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT 02285387.